Convective Instability of a Relativistic Ejecta Decelerated by a Surrounding Medium: An Origin of Magnetic Fields in Gamma-Ray Bursts? - Levinson, Amir (Astrophysical journal. Letters, 2009)
Global linear stability analysis of a self-similar solution describing a relativistic shell decelerated by an ambient medium is performed. The system is shown to be subject to the convective Rayleigh-Taylor instability, with a rapid growth of eigenmodes having angular scale much smaller than the causality scale. The growth rate appears to be largest at the interface separating the shocked ejecta and shocked ambient gas. The disturbances produced at the contact interface propagate in the shocked media and cause nonlinear oscillations of the forward and reverse shock fronts. It is speculated that such oscillations may affect the emission from the shocked ejecta in the early afterglow phase of gamma-ray bursts, and may be the origin of the magnetic field in the shocked circum-burst medium.